Perancangan Sistem Informasi Pengelolaan Surat Menyurat Berbasis Web Desa Sumberkarang - Izzatul Umami; Muhammad Tony Adam; Winarti Winarti (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The Along with the development of technology, correspondence activities which were originally done conventionally have turned more modern and sophisticated. Therefore, technological developments make it easier to manage community mobility documents in the village or district. The development of this technology is in the form of a website that can be accessed online to facilitate correspondence activities. The purpose of this research is to design a web-based correspondence management information system in Sumberkarang Village. This research method uses PIECES analysis. Based on the results of research and discussion, it is shown that in the implementation of the design information system to manage correspondence in Sumberkarang Village it runs properly and the results can be used to manage incoming and outgoing mail. The management of the correspondence can also be tested and proven by using the results of the Blackbox test.